Developments in Academic and Test Anxiety Among Students: International Trends and Treatment Strategies (Al-Farooq Journal of Sciences, 2025)
The study aimed to analyze research development in academic anxiety and test anxiety among students during 2015–2025 through a thematic review of Arabic and international studies. It sought to identify major research and methodological trends, psychological and educational factors associated with the phenomenon, and the main therapeutic strategies used to reduce it. The study adopted the descriptive-analytical approach and thematic analysis by classifying studies according to trends, methods, samples, theoretical frameworks, and findings. The results showed that academic anxiety and test anxiety are negatively associated with academic achievement, motivation, and self-confidence. Arabic studies tended to focus on description and diagnosis, whereas international studies showed greater attention to experimental interventions. The findings also highlighted the effectiveness of cognitive-behavioral therapy, relaxation, group counseling, self-regulation, and mindfulness in reducing students’ anxiety.
Keywords: Academic anxiety, test anxiety, students, thematic analysis, therapeutic strategies.